A new continent in the geographic distribution of the genus Oregoniplana (Platyhelminthes: Tricladida: Maricola), its rediscovery in South Africa and its molecular phylogenetic position. Issue 1 (13th April 2019) - Li, Wei-Xuan; Sluys, Ronald; Vila-Farré, Miquel; Chen, Jia-Jia; Yang, Ying; Li, Shuang-Fei; Wang, An-Tai
Abstract: Here we describe a new species for the genus Oregoniplana from the coast of China, representing the third species for the genus and the first record of this genus for Asia. The other species are known from Oregon, USA, and from South Africa. Specimens of the South African species, Oregoniplana pantherina, were recently rediscovered, forming the second record for the species, which provided the basis for a necessary re-description. Molecular data (18S rDNA and 28S rDNA) obtained for the new Chinese species facilitated determination of the position of the genus Oregoniplana in the phylogenetic tree of the marine triclads. We report molecular data also for species previously discovered in China, viz. Miroplana shenzhensis and Pentacoelum sinensis, thus enabling us to determine for the first time the phylogenetic position of the genus Miroplana . These new molecular data revealed that Pentacoleum sinensis occupies an unexpected position in the phylogenetic tree. Laboratory cultures of the new Chinese species provided information on food preferences and reproduction. Oregoniplana pantherina exhibits a peculiar kind of locomotion and an unusual resting position in which the animal has three points of contact on either side.